Female streetworking prostitution and HIV infection in Glasgow. Issue 6857 (3rd October 1992) - McKeganey, N.; Barnard, M.; Leyland, A.; Coote, I.; Follet, E.
Abstract : OBJECTIVES–To identify the extent of HIV infection and injecting drug use among female streetworking prostitutes in Glasgow; to estimate the size of the female streetworking prostitute population in the city; and to estimate the number of HIV positive women working as prostitutes on the streets in Glasgow. DESIGN–Observation and interviewing of female prostitutes over seven months in red light district; analysis of saliva samples for presence of antibodies to HIV; capture-recapture approach to estimating the size of the female streetworking prostitute population. SETTING–Glasgow. SUBJECTS–206 female streetworking prostitutes. MAIN OUTCOME MEASURES–Number of women with antibodies to HIV, self reported use of injecting drugs, history of contact with 206 women. RESULTS–Saliva samples were requested from 197 women; 159 (81%) provided samples. Four (2.5%, 95% confidence interval 0.7%-6.3%) of the samples were positive for HIV, all of which had been provided by women who injected drugs. Of the 206 streetworking women contacted 147 (71%) were injecting drug users. About 1150 women are estimated to work on the streets in Glasgow over a 12 month period. CONCLUSIONS–HIV is not as widespread among female prostitutes as many reports in the tabloid press suggest. A greater proportion of female streetworking prostitutes in Glasgow are injecting drugs than has been reported for other British cities.